Ambiguity Found in the Text Containing Local Wisdom - Suzana Rahman; Nunung Nurjannah (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2017)
Theories of semantics ‘ interpretation of meanings are not only discussing about speakers’ meaning and word or sentence meaning.They are also influenced by ambiguity. Ambiguity can cause different interpretation of meanings. One of the problems is caused byone has more than one meaning. The aim of this research entitled : “The Analysis of Ambiguity Found in the Texts containing Local Wisdom”. is to find out lexical ambiguity in the texts containing local wisdom. The choice of the texts can be in the form of brochures of some tourism objects around Cirebon, or the hystorical background of Cirebon and some other places of The Area III of Cirebon and Ciayu Maja Kuning. This research is regarded to be important due to the effect of ambiguity that can cause mis interpretation of meaning that will cause misunderstanding. The term lexical ambiguity follows the theories of Fromkin et.al (2002) and Kent Bach (2009). The data is taken from those texts that have been previously stated, then all the data willl be analyzed to know the type and occurence of the usage in those texts.After that the way how to disambiguate them will be described. The research method that is used in this research is descriptive qualitative from Creswell (1994).Findings : The words classes found to be ambiguous were: 46.6 % Nouns; 33.33 % Adjectives; 6.66% Verb; 6.66% Adverb. It also means that its occurances of ambiguites were mostly in nouns, adjectives, verb and adverb. The way to disambiguate the ambiguous words mostly by giving additional information required to clarify the meanings of those words in order to avoid ambiguity; only one using picture. Almost all the ambiguities were caused by having multiple meanings that are also called polysemious. Other researchers who are interested toknow more about ambiguity can use other kind of texts to elaborate the findings.Keywords: ambiguity, local wisdom content-text, lexical